Seleksi Awal Pejantan Sapi Bali Berbasis Uji Performans - Ni Wayan Patmawati; Ni Nyoman Trinayani; Mahmud Siswanto; I Nengah Wandia; I Ketut Puja (Veterinary Science and Medicine Journal, 2013)
Performance test is a preliminary selection to choose Bali cattle stud based on qualitative and quantitative characteristics, including measurement, weighing and observation. Performance test is  applied  on rapid growth of bull  (about 1 year of age) by comparing individual performance with the performance of the group average. The number of bulls that were subjected  the  Performance test  in 2011  was 61  bulls.  Based on Performance test, the best three of the performances  namely the score of 113.30, 109.46,and 104.2  were s selected to be potential stud candidates for next Zuriat test (progeny test).